Liver Transplantation Reverses Hepatic Myelopathy in 2 Children With Hepatitis A Infection. (9th January 2021) - Koul, Roshan; Lal, Bikrant Bihari; Pamecha, Viniyendra; Sarin, Shiv; Alam, Seema
Objectives: To report 2 children with acute hepatic myelopathy after hepatitis A infection who recovered completely after living donor liver transplantation. Methods: All the children admitted into liver intensive care unit (LICU) from November 1st 2018 to 31st October 2019, were evaluated for the neurological features. The data was collected from the admission register of the LICU unit in children below 15 years age. Medical records of these children were reviewed and data collected. Established clinical criteria were used to categorize the various grades of hepatic encephalopathy/myelopathy. Results: 37 children were seen over 1-year period between 6 months to 15 years age. There were 24 male(64.9%) and 13 females. Acute liver failure was seen in 19 (51.3%) and acute on chronic liver failure in 18 (48.7%). There were 10 cases of hepatitis A in acute liver failure group, 10 of 19 cases (52.6%), while Wilson's disease and undetermined etiology group formed the chronic group. 2 cases of hepatic myelopathy were seen in acute liver failure following hepatitis A infection. Both these children underwent live liver donor transplantation and recovered completely. Further in hepatitis A group, 3 children had spontaneous recovery, 4 died and 1 child was discharged with end of life care. Overall out of all 37 children with liver failure, 20 (54%) were discharged, 6 (16.2%) were advised end of life care and 11 (29.8%) died. Conclusion: Two cases (10.5%) of reversible hepatic myelopathy were seen in acute liver failure group of 19 cases. 18 out of 37 (48.6%) children had residual neurological features at discharge time.